2016
DOI: 10.3389/fnhum.2016.00191
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Brain Dynamics during Sentence Reading: A Fixation-Related Spectral Perturbation Analysis

Abstract: The present study investigated oscillatory brain dynamics during self-paced sentence-level processing. Participants read fully correct sentences, sentences containing a semantic violation and “sentences” in which the order of the words was randomized. At the target word level, fixations on semantically unrelated words elicited a lower-beta band (13–18 Hz) desynchronization. At the sentence level, gamma power (31–55 Hz) increased linearly for syntactically correct sentences, but not when the order of the words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 84 publications
(162 reference statements)
0
20
0
Order By: Relevance
“…Delta and theta findings reported in Peña and Melloni (2012) and Mai et al (2016) suggest that low-frequency oscillations are sensitive to prosodic and syllabic information, regardless of whether successful semantic and/or syntactic unification can be performed. Their effects appear to be different in nature than the theta increases reported in Bastiaansen et al (2010) and Vignali et al (2016), which only occurred in syntactically structured sentences and not word lists, and were interpreted as reflecting building of a memory trace of the unfolding linguistic input.…”
Section: Syntactic and Semantic Structure Buildingmentioning
confidence: 61%
See 3 more Smart Citations
“…Delta and theta findings reported in Peña and Melloni (2012) and Mai et al (2016) suggest that low-frequency oscillations are sensitive to prosodic and syllabic information, regardless of whether successful semantic and/or syntactic unification can be performed. Their effects appear to be different in nature than the theta increases reported in Bastiaansen et al (2010) and Vignali et al (2016), which only occurred in syntactically structured sentences and not word lists, and were interpreted as reflecting building of a memory trace of the unfolding linguistic input.…”
Section: Syntactic and Semantic Structure Buildingmentioning
confidence: 61%
“…Indeed, Srinivasan, Winter, and Nunez () found that while EEG detected frontal alpha and theta rhythms generated during a rest period, very little of the same activity was detected with MEG. On the other hand, the EEG study by Vignali et al () did not observe increased theta. The absence of a theta effect there may however be explained by the fact that this study used a naturalistic reading paradigm with eye‐tracking rather than the rapid serial visual presentation (RSVP) paradigm used in most studies reviewed so far.…”
Section: Violation Studiesmentioning
confidence: 78%
See 2 more Smart Citations
“…More generally, a large number of studies have documented increases in gamma-band response (GBR) amplitude during processing of meaningful words (compared to baseline) (e.g., Canolty et al, 2006; Edwards et al, 2010; Pei et al, 2011; Wu et al, 2011; Vignali et al, 2016). Most relevant to the present results, higher spectral power during processing of familiar items (words) vs. unfamiliar ones (pseudowords or non-words) has been found in English using MEG (Pulvermüller et al, 1996a) and ECoG (Canolty et al, 2007), in Finnish with EEG (Krause et al, 1998), in German with MEG (Eulitz et al, 1996), and in French, using intracortical recordings (Mainy et al, 2008), with remarkable consistency across languages, sensory modalities, and recording methods.…”
Section: Discussionmentioning
confidence: 99%